Exploring Future Research in Adapted Physical Education. Issue 3 (3rd July 2021) - Block, Martin E.; Haegele, Justin; Kelly, Luke; Obrusnikova, Iva
ABSTRACT: Quality physical education can play a critical role in helping students become more active, physically literate, and develop the skills and interests to remain physically active throughout their lives. The healthy, physically active student is more likely to be academically motivated, alert, and successful in school. Unfortunately, findings from multiple studies interviewing students with disabilities suggest that students with disabilities are often less active and feel more socially separated from the class compared to their classmates without disabilities in general physical education. Clearly, more research is needed to identify best practices or strategies for creating a positive learning environment in physical education for all students. This paper examines future research considerations based on what we currently know about the physical education experiences and concerns of students with disabilities as well as concerns voiced by general physical educators. Considerations include: (1) What evidence do we have and what evidence do we need to show students with 3 disabilities are receiving appropriate physical education whether included or in a separate setting? (2) What evidence do we have and what evidence do we need to show that physical educators are properly trained and qualified to provide physical education to students with disabilities? (3) What evidence do we have and what evidence do we need to show that particular curricular and teaching models are effective when including students with disabilities in general physical education and when working in small groups or one-on-one? (4) What evidence do we have and what evidence do we need to show that students with disabilities are socially part of the class and not simply physically present.